GABA Vesicles at Synapses: Are There 2 Distinct Pools? - Hablitz, John J. (2009)
Fast synaptic inhibition in the neocortex is mediated by the neurotransmitter GABA, acting on GABA(A) receptors. Neurotransmitters, including GABA, are stored in synaptic vesicles at presynaptic nerve terminals. A long-held assumption has been that evoked and spontaneous neurotransmissions draw on the same pools of vesicles. We review the evidence from FM1-43 studies supporting the contention that at least 2 distinct pools of GABA vesicles are present at inhibitory synapses in the rat neocortex. FM1-43 uptake during spontaneous vesicle endocytosis labels a vesicle pool within neocortical inhibitory nerve terminals that is released much more slowly (“reluctant” pool) than those vesicles loaded by electrical stimulation of afferent fibers or hyper-kalemic solutions. These multiple pools may play diverse roles in such processes as long-term depression and/or potentiating of inhibitory synaptic transmission, homeostatic plasticity of inhibitory activity, or developmental changes in inhibitory synaptic transmission.